Parental influence and teenagers' motivation to train for technological jobs - Breakwell, Clynis M. [Verfasser]; Fife-Schaw, Chris [Verfasser]; Devereux [Verfasser]; Schaw, Chris Fife- [Verfasser] (My University, 1988)
"While governments are making attempts to attract young people into scientific and technical training programmes, these have yet any significant impact on numbers taking such training. This paper reports findings from a large, cross-regional survey of factors influencing young people's (13-18-year-olds) motivations to take technological training. By focusing on teenagers' perceptions of the influence parents have exerted over their educational and occupational choices it has been possible to demonstrate that indirect, rather than direct, forms of parental influence are significant in the formation of this motivational state. The implications of these findings are discussed in relation to policy and our understanding of socialization processes. (author's abtract) ((en)) Der Beitrag berichtet über Ergebnisse einer überregionalen Umfrage unter 13 bis 18 Jahre alten englischen Jugendlichen, in der nach den Einflüssen auf die Motivation, sich in technischen Berufen ausbilden zu lassen, gefragt wurde. Es zeigt sich, dass der Einfluss der Eltern in der Wahrnehmung der Jugendlichen eher indirekten als direkten Einfluss auf die Berufswahl hat. (IAB)
Elterneinfluss und Motivation von Teenagern, sich in technischen Berufen ausbilden zu lassen
Keywords: S 1.3 Berufliche Erstausbildung; T 4.5 Soziologie; Jugendlicher; Einstellung; Technische Bildung; Familiale Sozialisation; Berufswahl